2014
DOI: 10.1016/j.joca.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Functional cartilage repair capacity of de-differentiated, chondrocyte- and mesenchymal stem cell-laden hydrogels in vitro

Abstract: Objective The long-term performance of cell seeded matrix based cartilage constructs depends on (1) the development of sufficient biomechanical properties, and (2) lateral integration with host tissues, both of which require cartilage specific matrix deposition within the scaffold. In this study, we have examined the potential of tissue-engineered cartilage analogs developed using different cell types, i.e., MSCs versus chondrocytes and de-differentiated chondrocytes, in an established “construct in cartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…This was consistent with previous studies which revealed differentiated MSCs expressed lower levels of COL 2 and higher levels of hypertrophic markers compared to chondrocytes2425. In contrast, some studies found the opposed evidence that the pre-differentiated MSC-seeded scaffolds produced enhanced or similar levels of COL 2 or AGC than chondroctyes26272829. The difference might be due to varied passage of the chondrocytes used in those studies.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with previous studies which revealed differentiated MSCs expressed lower levels of COL 2 and higher levels of hypertrophic markers compared to chondrocytes2425. In contrast, some studies found the opposed evidence that the pre-differentiated MSC-seeded scaffolds produced enhanced or similar levels of COL 2 or AGC than chondroctyes26272829. The difference might be due to varied passage of the chondrocytes used in those studies.…”
Section: Discussionsupporting
confidence: 90%
“…Allon et al [19] augmented polymers with adhesion proteins while Maher et al [18] used growth factor-augmented nanofibers. Fortier et al [16] and Rackwitz et al [39] augmented scaffolds with growth factors and stem cells, respectively, while Erickson et al [40] modulated the extent of mesenchymal stem cell maturation in the hopes of optimizing integration. Hunziker and Kapfinger [21] chose to partially, enzymatically digest the host cartilage in an effort to free chondrocytes that would be capable of migrating to the scaffold interface.…”
Section: Discussionmentioning
confidence: 99%
“…ACI is only applicable to small size (3-4 cm 2 ) focal lesions surrounded by healthy cartilage [15,28]. Other limitations are dedifferentiation of chondrocytes during culture expansion, the low amount of chondrocytes obtained and multiple surgical procedures involved [31,32]. Further, donor-site morbidity of cartilage and bone for chondrocyte and periosteum obtaining was observed [15,33,34].…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 99%